A finite element approach for the static and vibration analyses of functionally graded material viscoelastic sandwich beams with nonlinear material behavior. (15th October 2021) - Koutoati, Kouami; Mohri, Foudil; Daya, El Mostafa; Carrera, Erasmo
Abstract: A beam finite element model is proposed for the static and free vibration analyses of FGM sandwich beams with viscoelastic nonlinear material behavior. In the analysis, zigzag theory is adopted for the displacement fields. The damping results from the shear properties of the viscoelastic layer and its low stiffness. Timoshenko 1st order and Reddy's higher order shear models are implemented for static and vibration behaviors. Various viscoelastic frequency-dependent laws are considered. The resulting stiffness matrix is nonlinear and is frequency dependent. Solutions are possible according to a powerful asymptotic method combined with recent method for the power series terms. The efficiency of the present model is proven through simulations using 3D volume elements of Abaqus code, where new module for viscoelastic FGM materials is now available. The effects of power law index and boundary conditions on static, vibration and the damping properties of the viscoelastic sandwich FGM beam are investigated successfully. It is shown that the beam behavior is very sensitive on the loss factor. In vibration, the damping properties are nonlinearly power law index dependent. The boundary conditions have an incidence on the vibration modes. The cantilever case is particular and interesting that needs an optimization process.